2015
DOI: 10.1139/cjfr-2014-0138
|View full text |Cite
|
Sign up to set email alerts
|

Forest forecasting with vegetation models across Russia

Abstract: Vegetation models are essential tools for projecting large-scale land-cover response to changing climate, which is expected to alter the distribution of biomes and individual species. A large-scale bioclimatic envelope model (RuBCliM) and an individual species based gap model (UVAFME) are used to simulate the Russian forests under current and future climate for two greenhouse gas emissions scenarios. Results for current conditions are compared between models and assessed against two independent maps of Russian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…It is an object-oriented version of FAREAST (Yan and Shugart 2005). Simulated species biomass, composition, and basal area have been validated along an elevation gradient in northeastern China and against forest type at sites in eastern Russia (Yan and Shugart 2005), against species inventory data from 44 forest locations spanning from eastern to western Russia (Shuman et al 2014), and against dominant species and forest biomes from a bioclimatic envelope model and two observation-based maps across Russia (Shuman et al 2015). A detailed description of UVAFME can be found in Supplement S2 available at stacks.iop.org/ERL/12/035003/mmedia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an object-oriented version of FAREAST (Yan and Shugart 2005). Simulated species biomass, composition, and basal area have been validated along an elevation gradient in northeastern China and against forest type at sites in eastern Russia (Yan and Shugart 2005), against species inventory data from 44 forest locations spanning from eastern to western Russia (Shuman et al 2014), and against dominant species and forest biomes from a bioclimatic envelope model and two observation-based maps across Russia (Shuman et al 2015). A detailed description of UVAFME can be found in Supplement S2 available at stacks.iop.org/ERL/12/035003/mmedia.…”
Section: Methodsmentioning
confidence: 99%
“…UVAFME is used to simulate species composition and biomass at 31 010 gridded sites with a spatial resolution of 23 km  23 km for coverage across Russia. Site and species parameters are derived as in Shuman et al (2015) and summarized in Supplement S2. Historical daily temperature and precipitation conditions at each site are derived from statistical distributions of mean monthly temperature and precipitation from 60 years of weather station data for the period from 1941 to 2001 (NCDC 2005a(NCDC , 2005b.…”
Section: Model Simulationsmentioning
confidence: 99%
“…These observations thus support the modelled shift in vegetation zones and the change in vegetation type composition and productivity. Likewise, other models with dynamic vegetation also have shown a strong expansion of broadleaved forests at the southern edge of the Siberian region in response to warming (Shuman et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…The University of Virginia Forest Model Enhanced simulates the regeneration, growth, and death of individual trees on independent patches of a forested landscape, with each patch/ plot experiencing the same site and climate conditions. A complete description of the equations and subroutines within UVAFME can be found in Shuman et al (2015) and in the UVAFME User's Manual in Foster et al (2017). Plots are assumed to have no direct horizontal spatial interactions with one another.…”
Section: Model Description and Updatesmentioning
confidence: 99%
“…New trees can regenerate each year based on climate and environmental conditions, disturbance occurrence, species-specific tolerances, and species' seedbanks (which are also modified each year based on site and climate conditions). A complete description of the equations and subroutines within UVAFME can be found in Shuman et al (2015) and in the UVAFME User's Manual in Foster et al (2017). This model has been updated and parameterized for the southern Rocky Mountains (Foster et al 2015, and it was found that model output on size structure and speciesspecific biomass agreed with inventory data within the subalpine zone.…”
Section: Model Description and Updatesmentioning
confidence: 99%